A Complete Sequence and Transcriptomic Analyses of Date Palm (Phoenix dactylifera L.) Mitochondrial Genome - Fang, Yongjun; Wu, Hao; Zhang, Tongwu; Yang, Meng; Yin, Yuxin; Pan, Linlin; Yu, Xiaoguang; Zhang, Xiaowei; Hu, Songnian; Al-Mssallem, Ibrahim S.; Yu, Jun (PloS one, 2012)
Based on next-generation sequencing data, we assembled the mitochondrial (mt) genome of date palm (Phoenix dactylifera L.) into a circular molecule of 715,001 bp in length. The mt genome of P. dactylifera encodes 38 proteins, 30 tRNAs, and 3 ribosomal RNAs, which constitute a gene content of 6.5% (46,770 bp) over the full length. The rest, 93.5% of the genome sequence, is comprised of cp (chloroplast)-derived (10.3% with respect to the whole genome length) and non-coding sequences. In the non-coding regions, there are 0.33% tandem and 2.3% long repeats. Our transcriptomic data from eight tissues (root, seed, bud, fruit, green leaf, yellow leaf, female flower, and male flower) showed higher gene expression levels in male flower, root, bud, and female flower, as compared to four other tissues. We identified 120 potential SNPs among three date palm cultivars (Khalas, Fahal, and Sukry), and successfully found seven SNPs in the coding sequences. A phylogenetic analysis, based on 22 conserved genes of 15 representative plant mitochondria, showed that P. dactylifera positions at the root of all sequenced monocot mt genomes. In addition, consistent with previous discoveries, there are three co-transcribed gene clusters-18S-5S rRNA, rps3-rpl16 and nad3-rps12-in P. dactylifera, which are highly conserved among all known mitochondrial genomes of angiosperms.